2015
DOI: 10.1002/lary.25521
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic Obstructive Sialadenitis Symptoms Questionnaire to assess sialendoscopy‐assisted surgery

Abstract: The COSS questionnaire is a novel survey instrument to measure obstructive sialadenitis symptom severity that could be helpful in defining outcomes of SASDS. COSS scores under 10 correlate with complete resolution of symptoms, whereas scores between 10 and 25 correlate with partial resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 41 publications
(105 citation statements)
references
References 22 publications
4
99
0
2
Order By: Relevance
“…In a recent retrospective study, we showed that patients who reported complete symptom resolution had COSS scores of less than 10; those with partial resolution of symptoms had COSS scores between 10 and 25; and those with no resolution of symptoms had COSS scores above 25. Based on these correlations, the survey scores were categorized accordingly.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…In a recent retrospective study, we showed that patients who reported complete symptom resolution had COSS scores of less than 10; those with partial resolution of symptoms had COSS scores between 10 and 25; and those with no resolution of symptoms had COSS scores above 25. Based on these correlations, the survey scores were categorized accordingly.…”
Section: Methodsmentioning
confidence: 91%
“…The recently described COSS questionnaire is a self‐administered 20‐question survey based on sialadenitis symptoms, including salivary gland pain, tenderness, and swelling during and in between meals the noticeability by others, level of embarrassment, xerostomia, too much saliva, purulent exudate, bloody exudate, interference with swallowing, speaking, mouth opening, chewing, sleep and daily activities. The questionnaire is scored on a scale of 0 to 100.…”
Section: Methodsmentioning
confidence: 99%
“…However, the retrospective, cross-sectional design of their study is a clear limitation. In 2016, Aubin-Pouliot et al [35] introduced the Chronic Obstructive Sialadenitis Symptoms (COSS) questionnaire to quantify sialadenitis-specific symptoms and to assess the impact of sialendoscopy-assisted surgery. The COSS survey evaluates the sialadenitis symptoms and impact of the symptoms on daily functions and emotional well-being, measuring also the HRQoL [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Aubin-Pouliot et al [35] introduced the Chronic Obstructive Sialadenitis Symptoms (COSS) questionnaire to quantify sialadenitis-specific symptoms and to assess the impact of sialendoscopy-assisted surgery. The COSS survey evaluates the sialadenitis symptoms and impact of the symptoms on daily functions and emotional well-being, measuring also the HRQoL [35, 36]. A prospective study consisting of 39 patients showed that patients with sialolithiasis as well as patients with submandibular problems showed a greater COSS score and symptom improvement than patients without sialolithiasis or patients with parotid symptoms, in accord with our findings [36].…”
Section: Discussionmentioning
confidence: 99%
“…We have developed the COSS questionnaire (Appendix 1) to measure sialadenitis‐specific symptoms. We have demonstrated that the COSS questionnaire is a sensitive tool for evaluation of sialadenitis‐specific symptoms that correlates with degree of symptom resolution beyond other quality‐of‐life instruments .…”
Section: Methodsmentioning
confidence: 99%